Reader Inspects BAR Restoration of an Israelite Village - Epstein, David (The Biblical archaeology review, 1979)
The early Israelite site of Izbet Sartah, believed to be Biblical Ebenezer (1 Samuel 4), is inauspiciously located in the midst of the town dump of modern day Rosh Haayin. I went to Izbet Sartah to see the recently completed preservation work. (See "BAR Readers to Restore Israelite Village from Days of the Judges," […]